Efficacy and safety of monotherapy and combination therapy of oral minoxidil for androgenetic alopecia: a structured review - Jahan, Safrin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.